Nilai Moral Pada Karya Tari ”Terumpak” - Valentin, Gadis (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This research aims to reveal the moral values contained in the dance work ”Terumpak” with the background of the Bangka Belitung myth about the grip of spirits due to breaking the taboos and customs that exist in a certain place. This research uses a qualitative approach to analyze movement symbols in dance. This research shows that the ”Terumpak” dance is not just entertainment but is also a communication medium that is rich in meaning and cultural values. It is hoped that the results of this research will increase insight into the role of dance in preserving moral values in society.